Antimicrobial peptides from marine animals: Sources, structures, mechanisms and the potential for drug development - Wang, Shuocun; Fan, Liming; Pan, Hanyu; Li, Yingying; Qiu, Yan; Lu, Yiming (Frontiers in Marine Science, 2023)
The emergence of antibiotic-resistant bacteria has become a major challenge in current clinical treatment. As essential natural molecules involved in innate immunity, antimicrobial peptides (AMPs) have the potential to break the limits of antibiotic resistance. While AMPs are widely presented in various organisms on this planet, the marine environment is unique in generating a large number of AMPs that exhibit characteristic structures and functions. This review summarizes the structures and mechanisms of action of AMPs derived from invertebrates, fish, amphibians, reptiles, and mammals in the ocean. The comparison of AMPs from organisms in different habitats demonstrates the preference of Arg (arginine) and Leu (leucine) in marine AMPs, which might be associated with the adaptation to the unique features of bacterial membranes in marine environments. In addition, the potential and applications of marine AMPs for the development of novel antibiotics are also described. These summaries are expected to provide a reference for the development and utilization of marine resources in drug development or aquiculture.